SYSTEM OF ACTIONS FOR THE IMPROVEMENT OF INTEGRATING FIELD PRACTICE IN HIGHER EDUCATION - Armiñana-García, Rafael (2020)
The investigative work presents a system of actions to carry out fi eld work with an integrative character and with an ecosystem approach and confronting climate change in the Bachelor of Education career Biology-Geography in Cuba, to enhance the future professional performance of graduates, by promoting Environmental Education and sustainable development in the centers of this level of education for the terminal years in the selected fi eld practice polygons. The diagnosis was made to determine the diffi culties that affect fi eld work realization in an integrative way. To mitigate the diffi culties detected, the system of actions whose contribution to the theory is given in its conception is proposed where the interaction between its components allows fulfilling the social order exposed in the professional model. The components that make up the system are: a theoretical block made up of the work of the professors and students cabinet; a practical block that includes the procedures for carrying out the actions and a conclusions block where the interrelation between theory and practice is corroborated. It shows the systematization and updating of new content in correspondence with the updating of the foundations of environmental education and the requirements for using the system. The system is submitted to experts' criteria declaring it pertinent and is put into practice from the academic year 2018 - 2019 with excellent results. Keywords: Environmental Education – integrative field practice – system